Application of Two Blastocyst Biopsy Strategies in Preimplantation Genetic Testing Treatment and Assessment of Their Effects - Yang, Han; Yang, Dandan; Zhu, Qi; Wang, Kaijuan; Zhang, Chao; Chen, Beili; Zou, Weiwei; Hao, Yan; Ding, Ding; Yu, Zhaojuan; Ji, Dongmei; Chen, Dawei; et al. (Frontiers in Endocrinology, 2022)
Background: Blastocyst biopsy has become the most mainstream biopsy method. Currently, there are two blastocyst biopsy strategies. Many studies have compared the advantages and disadvantages between blastomere and blastocyst biopsy, but fewer articles have compared the two blastocyst biopsy strategies. For the moment, no published studies have explored the entire set of information on embryo development, next-generation sequencing results, and clinical outcomes, including the baby’s health status with the two blastocyst biopsy strategies. Methods: A total of 323 preimplantation genetic testing cycles from April 2018 to May 2020, including 178 cycles with Strategy A and 145 cycles with Strategy B. Strategy A was to create a laser-assisted zona pellucid opening for cleavage embryo on the third day after insemination, but Strategy B was not. Strategy A performed a biopsy for artificially assisted hatching blastocysts, while Strategy B performed a biopsy for expanded blastocysts on day 5 or 6. In this study, embryo development, next-generation sequencing results, pregnancy outcomes, and offspring health of the two strategies were compared and analyzed. Results: There were no statistical differences between the two groups in the rate of fertilization, blastocyst and abortion. The rate of cleavage from Strategy A was slightly higher than Strategy B, and the rate of high-quality cleavage embryo was lower than Strategy B, while the rate of high-quality blastocyst was higher than Strategy B. The rate of no-results blastocyst was significantly lower than Strategy B. In particular, the rate of biochemical pregnancy, clinical pregnancy, and live birth of Strategy A were significantly lower than those of Strategy B. The average Apgar scores of newborns were ≥8 in both groups, and there was no significant difference in average height and weight. In Strategy A, a baby was born with thumb syndactyly, and Strategy B had no congenital disabilities. Conclusions: Blastocyst biopsy strategy without laser-assisted zona pellucid drilling on day 3 achieves better clinical treatment effects. Therefore, Strategy B is an optimal treatment regime for PGT.